PENGARUH PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM, DANA ALOKASI KHUSUS DAN PERTUMBUHAN EKONOMI TERHADAP BELANJA DAERAH PERIODE 2012 - 2015 (Studi Pada Pemerintah Kabupaten/Kota Di Jawa Timur) - Akmaludin ust (JURNAL EKOBIS DEWANTARA, 2018)
The aim of this study was to examine the effect of locally generated revenue, general allocation funds, special allocation, economic growth to regional expenditure in the period 2012-2015. The population in this study was all of the district of province in East java of the year 2012-2015. The research samples was determined by using jenuh sampling technique which means the total of population is the sample, numbered 38 diatricts. The data that used in this study was obtained from secondary source. That was from https://jatim.bps.go.id. And the central cervice of statistic in the form of annual financial statements in the period 2011-2015. The This study used multiple linear regression method as an analysis technique. The regression test results showed that locally generated revenue, general allocation funds, special allocation, economic growth simultaneously have a significant positive effect on regional expenditure. Partially, locally generated revenue has a significant positive effect on regional expenditure. General allocation funds has a significant positive effect on regional expenditure, special allocation funds has a significant positive effect on regional expenditure and economic growth has no significant positive effect to regional expenditure on of the district of province in East java in the year 2012-2015. The influence of independent variables can be seen from the value of the coefficient of determination (R2). The coefficient of determination (R2) in this study was amounting to 0.903, which means locally generated revenue, general allocation funds, special allocation, economic growth give positive influence on the regional expenditure up to 90.3%, while 9.7% influenced by other variables outside the study.